Deskripsi Penggunaan Gadget Melalui Pelayanan Paud Holistik Integratif di TK Negeri Pembina Salakan - Maisarah A.W.A Karim; Meisin Yuan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
he digital era brings significant changes in various aspects of life, including early childhood (ECD) parenting patterns. Easy access to gadgets ultimately results in excessive use that has a negative impact on children's growth and development. This study aims to examine strategies for overcoming the impact of excessive gadget use on ECD through optimizing Holistic Integrative Early Childhood Education (PAUD HI) services at TK Negeri Pembina Salakan. The methods used are literature studies and participatory observations of the implementation of the PAUD HI program. The results of the study indicate that the PAUD HI approach that includes integrated education, health, nutrition, care, protection, and welfare services can be an effective solution. At TK Negeri Pembina Salakan, its implementation is realized through learning activities that stimulate all aspects of development, active involvement of parents in digital parenting education, provision of an environment rich in non-gadget stimulation, and collaboration with health services and the community. It is concluded that PAUD HI has a strategic role in mitigating the negative risks of gadgets and supporting optimal growth and development of ECD.